2018
DOI: 10.4040/jkan.2018.48.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parenting Stress and Controlling Parenting Attitudes on Problem Behaviors of Preschool Children: Latent Growth Model Analysis

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0)If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. Purpose: This study was conducted to examine the longitudinal effects of parenting stress and parental control attitudes on problem behaviors in preschool children, using a latent growth model. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
(14 reference statements)
2
18
0
1
Order By: Relevance
“…4 In many studies, it has been reported that due to negative life events and stress, symptoms such as anxiety, depression, lethargy, disturbed social interaction, and loss of appetite, are seen in children. [36][37][38][39][40] Children who have become distant from their social circles and their friends with the closure of schools, experience a significantly restricted social life, and with the decrease in activities, not only become isolated at home and may become increasingly anxious about contracting infection. In this context, the role of parents in the alleviation of the psychological effects of isolation, is very important.…”
Section: Discussionmentioning
confidence: 99%
“…4 In many studies, it has been reported that due to negative life events and stress, symptoms such as anxiety, depression, lethargy, disturbed social interaction, and loss of appetite, are seen in children. [36][37][38][39][40] Children who have become distant from their social circles and their friends with the closure of schools, experience a significantly restricted social life, and with the decrease in activities, not only become isolated at home and may become increasingly anxious about contracting infection. In this context, the role of parents in the alleviation of the psychological effects of isolation, is very important.…”
Section: Discussionmentioning
confidence: 99%
“…В этом должны помогать программы общественного здравоохранения для детей и подростков, проживающих в районах, пострадавших от пандемии. При надлежащей поддержке со стороны медицинских работников, семей и других социальных систем (например, школ) дети и подростки смогут преодолеть стрессовое состояние и стабилизировать эмоциональное и психическое здоровье [20].…”
Section: ранние исследования поведенческих и эмоциональных реакций киunclassified
“…In children at key stages, the interruption of social and educational activities for many months can have a higher impact on their development. Recent investigations on the consequences of stressful situations in the mental health of small children show that anxiety, depression, lethargy, damaged social interaction and poor appetite are the most usual psychological manifestations, while at the physiological level a weakened immune system can be observed [5][6][7][8] .Recently, Fegert et al 9 established the impact of the phases of the pandemic on the mental health of children and adolescents. They include in their study certain risk factors and difficulties that children have to face in the first phase of the COVID-19 pandemic: children have not been allowed to use the usual playgrounds, social group activities are forbidden, sports clubs are closed, social relationships have been strongly limited to close relatives, contact with peers has been forbidden, school closures, loss of education time, and loss of daily structure.…”
mentioning
confidence: 99%
“…In children at key stages, the interruption of social and educational activities for many months can have a higher impact on their development. Recent investigations on the consequences of stressful situations in the mental health of small children show that anxiety, depression, lethargy, damaged social interaction and poor appetite are the most usual psychological manifestations, while at the physiological level a weakened immune system can be observed [5][6][7][8] .…”
mentioning
confidence: 99%